2012
DOI: 10.1007/s11524-011-9644-8
|View full text |Cite
|
Sign up to set email alerts
|

Health Impact Assessment in a Network of European Cities

Abstract: The methodology of health impact assessment (HIA) was introduced as one of four core themes for Phase IV (2003IV ( -2008 of the World Health Organization European Healthy Cities Network (WHO-EHCN). Four objectives for HIA were set at the beginning of the phase. We report on the results of the evaluation of introducing and implementing this methodology in cities from countries across Europe with widely differing economies and sociopolitical contexts. Two main sources of data were used: a general questionnaire d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
1
10
0
3
Order By: Relevance
“…A survey of participants in the European Healthy Cities Network reported that the following factors facilitated the use of an HIA: political support, training in HIA, collaboration with a public health institution or agency, a culture of intersectoral collaboration, a supportive national policy, and access to HIA expertise (47). The same survey reported the following barriers to HIA implementation: lack of skill, knowledge, and experience about HIAs; lack of a legal basis for implementation; and lack of political support (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of participants in the European Healthy Cities Network reported that the following factors facilitated the use of an HIA: political support, training in HIA, collaboration with a public health institution or agency, a culture of intersectoral collaboration, a supportive national policy, and access to HIA expertise (47). The same survey reported the following barriers to HIA implementation: lack of skill, knowledge, and experience about HIAs; lack of a legal basis for implementation; and lack of political support (47).…”
Section: Discussionmentioning
confidence: 99%
“…The same survey reported the following barriers to HIA implementation: lack of skill, knowledge, and experience about HIAs; lack of a legal basis for implementation; and lack of political support (47). In a related report, factors enhancing the acceptability of recommended interventions included documented benefits, adaptability for stakeholder needs, an evidence base for the work, engagement of stakeholders, and the use of simple, clear language (48).…”
Section: Discussionmentioning
confidence: 99%
“…Il est évidemment envisageable de poursuivre dans la lignée entamée en période 3 en renforçant les actions mises en oeuvre sans modifier ou ajouter de changements majeurs, au risque de lire des résultats similaires et consolidés, et de mettre en évidence des barrières similaires dans quelques années. Nous abondons dans le sens de Ison pour qui l'amélioration des EIS ne doit pas perdre de vue la consolidation des acquis 3 (Ison, 2012). Il est aussi important de « s'assurer que les apprentissages soient réutilisés pour permettre une meilleure intégration de la prise en compte de la santé dans les politiques et les décisions en général 4 .…”
Section: Conclusion Et Discussionunclassified
“…Il est aussi important de « s'assurer que les apprentissages soient réutilisés pour permettre une meilleure intégration de la prise en compte de la santé dans les politiques et les décisions en général 4 . » (Ison, 2012).…”
Section: Conclusion Et Discussionunclassified
“…Les EIS sont alors motivées par la volonté d'intégrer la santé dans toutes les politiques ou de contribuer à la réduction des inégalités sociales de santé. Parce que l'EIS requiert, d'une part, l'implication de la société civile et repose, d'autre part, sur le partenariat entre les institutions et les acteurs impliqués dans le projet concerné, l'OMS a considéré cette démarche comme une porte d'entrée pour introduire la santé dans les autres politiques et l'a inscrite dans le programme du réseau des Villes-Santé pour la période 2004-2008(Ison, 2013, ce qui a largement contribué à sa diffusion au niveau local , notamment en France. Cave (2015) considère que la voie réglementaire et le plaidoyer sont deux approches importantes et complé-mentaires pour le développement de l'EIS.…”
Section: Françoise Jabot Et Anne Roué Le Gall Quelle Plus-value De Launclassified